Microcontroller-based Artificial Lighting to Help Growth the Seedling Pakcoy - Mas Aly Afandi; Irmayatul Hikmah; Chandra Agustinah (Jurusan Teknik Elektro Universitas Andalas, 2021)
Improving efficiency and quality in farming activities is important reason of developing technology to support agriculture. Technology in agriculture such as image processing, Internet of Things (IoT), Artificial Intelligence, Big Data, and Artificial Lighting gives increasing trends. Artificial lighting technology has high impact to support agriculture in an area that has low sun light intensity such as in rainy season. Farmer has a difficulty to cultivating plant especially in early stage in rainy season. This problem happen because of the intensity of sun light is very minimum. Artificial lighting is a technology to solve early stage cultivating problem in rainy season. This technology can support agriculture for cultivating plant with minimum sun light. Artificial lighting contains light emitting diode (LED) that is laid out as an array. This research goal is to make an artificial lighting prototype to support early stage cultivating. Pakcoy is a plant that used to observe artificial lighting impact for early stage Pakcoy cultivation. This research shows Pakcoy plant placed in the prototype gives significant growth compared with a plant which placed in low light room. Pakcoy plant in artificial lighting gives 2 – 4 leaves, the height is 1.5 – 5cm, and from 18 seeds 10 is grow. This research can conclude that artificial lighting prototype can support early stage Pakcoy cultivation.